On the Same Wavelength? Differing Geopolitical Positionalities and Voluntary Return and Reintegration in Ghana - Ester Serra-Mingot; Markus Rudolf (Journal of International Migration and Integration, 2022)
This paper explores the range of experiences of "voluntary" return to Ghana, based on the different positionalities of migrants set against migration and return regimes and broader socio-economic inequalities. The cases illustrate how geopolitical relations shape migrants' mobilities, highlighting the unequal relations between different actors in the countries of origin and destination; primarily these are the migrants, their relatives, and communities of origin. Conflicting interests and expectations of these actors, as much as differing return policies, create unequal options and expectations of mobility. Migrant journeys, regardless the age, gender, legal status or social class, are always geopolitical journeys. The diverging experiences of return, thus, depend not only on the individual situations, but also on the broader politicized relations and interests between stakeholders in the migration and return processes.
Keywords: 300; Return migration; Reintegration; Ghana; Assisted voluntary return and reintegration (AVRR)